Faktor Pengambilan Keputusan Petani dalam Alih Fungsi Lahan Pertanian: Review - Sholeh, Mohammad Shoimus; Nazizah, Fitrotin; Kristiana, Lia; Nurmalasari, Yanti (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Agricultural land has economic value as a support for the needs of boards, clothing and food. Optimal management of agricultural land will support realizing food security, increasing competitiveness and reducing poverty. However every year there is a conversion of agricultural land to non-agricultural land both from farmers and non-farmers. The conversion of land carried out by farmers will cause a reduction in agricultural yields which are obtained every year, but farmers make the decision to convert the land. Therefore, it is necessary to study the decision-making factors of farmers in carrying out the conversion of agricultural land to non-agricultural land. The method used in this research is the literature review method. The results of several studies regarding land conversion show that the most influencing factor for farmers to decide to convert land is farming income with a percentage of 58.82% from 17 studies. That is if the income of farming can meet the needs of farmers, then the possibility of farmers to carry out land conversion is less. Therefore, the government's role needs to be increased and energized from various related agencies so that farmers' income can increase.